A comparison of fentanyl with pethidine for pain relief during childbirth: a randomised controlled trial. (5th January 2015) - Fleet, J; Belan, I; Jones, MJ; Ullah, S; Cyna, AM
<x xml:space="preserve">Abstract</x> Objective To compare the efficacy of fentanyl administered via the subcutaneous (s.c.) or intranasal (i.n.) route with intramuscular (i.m.) pethidine in labouring women requesting analgesia. Design A randomised controlled trial three‐armed, parallel‐design. Setting A regional hospital and the largest tertiary maternity centre in South Australia. Sample One hundred and fifty‐six healthy parturients birthing at term. Methods Women were randomised to receive s.c. fentanyl (n = 53), i.n. fentanyl (n = 52), or i.m. pethidine (n = 51). The outcomes were analysed by intention‐to‐treat. Main outcome measures Pain scores measured before and 30 minutes after opioid administration. Results All groups reported clinically significant reductions in pain scores (mean range 1.2–1.6; P < 0.001), with no significant differences between groups. Significantly more women in the fentanyl groups reported satisfaction with using the study drug again, compared with women receiving i.m. pethidine (82.9% i.n. fentanyl, 80.6% s.c. fentanyl, and 44.0% i.m. pethidine; P < 0.01). Women in the fentanyl groups experienced less sedation (i.n. fentanyl 7.3%, s.c. fentanyl 2.9%, i.m. pethidine 44%; P ≤ 0.03), shorter labours by at least 2 hours (P < 0.05), and fewer difficulties establishing breastfeeding (78.8% i.m. pethidine, 39.4% i.n. fentanyl, and 44.0% s.c. fentanyl; P < 0.01). Neonates in the pethidine group were more likely to require nursery admission (P < 0.02). Conclusions Fentanyl administered by s.c. and i.n. routes is as efficacious in relieving labour pain as i.m. pethidine, but resulted in greater satisfaction, less sedation, shorter labour, fewer nursery admissions, and fewer difficulties in establishing breastfeeding. Fentanyl appears to be a suitable alternative to pethidine when providing parenteral pain relief to labouring women.